Comparison of methods available for identification of Mycobacterium chimaera. (April 2018) - Lecorche, E.; Haenn, S.; Mougari, F.; Kumanski, S.; Veziris, N.; Benmansour, H.; Raskine, L.; Moulin, L.; Cambau, E.; ,
Abstract: Objectives: Mycobacterium chimaera is a recently described nontuberculous mycobacterium belonging to the Mycobacterium avium complex (MAC). Because this species is implicated in a worldwide outbreak due to contaminated heater–cooler unit water tanks during open-heart surgery, it has become mandatory for clinical microbiology laboratories to be able to differentiate M. chimaera from the other MAC species, especially M. intracellulare . Such identification has so far been restricted to specialized laboratories because it required the analysis of several gene sequences. The aim of this study was to evaluate commercial methods for identifying M. chimaera with regard to the reference gene sequencing ITS, the internal transcribed spacer 16–23S. Methods: Forty-seven clinical and environmental isolates including 41 MAC were identified by (a) PCR sequencing of the ITS and hsp65 genes, (b) three molecular biology kits (INNO-LiPA Mycobacteria, GenoType Mycobacterium CM and GenoType NTM-DR) and (c) matrix-assisted desorption ionization–time of flight mass spectrometry (MALDI-TOF MS) using Microflex LT. Results: There was a high concordance for species determination between the reference ITS sequencing and the GenoType NTM-DR test (39/41, 95%), the INNO-LiPA Mycobacteria test (38/41, 93%) and the hsp65 sequencing (38/41, 93%). The GenoType Mycobacterium CM test did not distinguish M. chimaera from M. intracellulare . MALDI-TOF MS distinguished two M. chimaera – M. intracellulare groups separated from M. avium and from the other mycobacterial species on a score-oriented dendrogram, but it also failed to differentiate the two species. Conclusions: INNO-LiPA Mycobacteria and GenoType NTM-DR are efficient assays for M. chimaera identification in clinical microbiology laboratories.